2019
DOI: 10.1242/dmm.037390
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing regeneration after acute kidney injury by promoting cellular dedifferentiation in zebrafish

Abstract: Acute kidney injury (AKI) is a serious disorder for which there are limited treatment options. Following injury, native nephrons display limited regenerative capabilities, relying on the dedifferentiation and proliferation of renal tubular epithelial cells (RTECs) that survive the insult. Previously, we identified 4-(phenylthio)butanoic acid (PTBA), a histone deacetylase inhibitor (HDI), as an enhancer of renal recovery, and showed that PTBA treatment increased RTEC proliferation and reduced renal fibrosis. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 106 publications
(157 reference statements)
1
17
0
Order By: Relevance
“…Locally synthesized RA inhibits the pro-inflammatory M1 phenotype, thus reducing macrophage-dependent damage and activating RA signaling in the damaged tubular epithelium, which in turn promotes the selective activation of M2 macrophages ( 68 ). It was previously demonstrated that the effect of 4-(phenylthio) butanoic acid (PTBA) on the proliferation of RTECs is dependent on RA signaling ( 69 ). The therapeutic characteristics of PTBA are not limited to the kidney, since PTBA also increases the proliferation of cardiomyocytes and reduces fibrosis after heart injury in adult zebrafish.…”
Section: Signal Transduction Of Macrophages In Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Locally synthesized RA inhibits the pro-inflammatory M1 phenotype, thus reducing macrophage-dependent damage and activating RA signaling in the damaged tubular epithelium, which in turn promotes the selective activation of M2 macrophages ( 68 ). It was previously demonstrated that the effect of 4-(phenylthio) butanoic acid (PTBA) on the proliferation of RTECs is dependent on RA signaling ( 69 ). The therapeutic characteristics of PTBA are not limited to the kidney, since PTBA also increases the proliferation of cardiomyocytes and reduces fibrosis after heart injury in adult zebrafish.…”
Section: Signal Transduction Of Macrophages In Akimentioning
confidence: 99%
“…The therapeutic characteristics of PTBA are not limited to the kidney, since PTBA also increases the proliferation of cardiomyocytes and reduces fibrosis after heart injury in adult zebrafish. This provides a critical insight into the mechanism by which PTBA enhances repair in AKI ( 69 ). In addition, it has also been reported that RA has a beneficial effect on CI-AKI in vivo and in vitro .…”
Section: Signal Transduction Of Macrophages In Akimentioning
confidence: 99%
“…Several drugs have been shown to improve kidney regeneration, and, among those, histone deacetylase (HDAC) inhibitors (HDACis) may be a promising therapeutic option for the treatment of AKI [ 97 , 98 , 99 , 100 , 101 , 102 ]. HDACs form a group of enzymes involved in multiple cellular processes by removing the acetyl group from histone or nonhistone proteins [ 103 ].…”
Section: Tubular Progenitorsmentioning
confidence: 99%
“…Using a simple bioreactor-based method for generating human kidney organoids from iPSCs [25,26], we hypothesized hemin-induced ROS-mediated injury and fibrosis could be a valuable tool for evaluating potential therapeutics. Here, we show how this fibrotic model can be used to test the efficacy of promising anti-fibrotic agents such as 4-(phenylthio)butanoic acid (PTBA), which we have previously shown can ameliorate injury and fibrosis in mouse models of AKI [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%